1965
DOI: 10.3181/00379727-118-29794
|View full text |Cite
|
Sign up to set email alerts
|

Production of Interferon by Human Mononuclear Leucocytes.

Abstract: The production of interferon by suspensions of human leucocytes has been previously demonstrated(1). The present series of experiments was performed to determine whether (a) mononuclear cells or (b) polymorphonuclear leucocytes or (c) both cell types were responsible for the interferon produced under these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

1965
1965
1977
1977

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 2 publications
(3 reference statements)
0
10
0
1
Order By: Relevance
“…With one exception, the smallpox vaccine used contained live vaccinia virus, and the possibility that replication of vaccinia in leukocytes contributed to the response could not be ruled out. Many other studies have demonstrated interferon production in cultured leukocytes stimulated by vaccinia virus (12,13) as well as by other viruses (14,15). Furthermore, cultures of leukocytes from animals immune to a given virus produced greater amounts of interferon when exposed to that virus than similar cultures from nonimmune animals (15).…”
mentioning
confidence: 97%
“…With one exception, the smallpox vaccine used contained live vaccinia virus, and the possibility that replication of vaccinia in leukocytes contributed to the response could not be ruled out. Many other studies have demonstrated interferon production in cultured leukocytes stimulated by vaccinia virus (12,13) as well as by other viruses (14,15). Furthermore, cultures of leukocytes from animals immune to a given virus produced greater amounts of interferon when exposed to that virus than similar cultures from nonimmune animals (15).…”
mentioning
confidence: 97%
“…We now know that leukocytes, both polymorphs and mononuclears, can produce interferon. 19,20 Not all microorganisms are destroyed in phagocytes. Indeed, the inflammatory reaction seems at times to accelerate the spread of infection.…”
Section: Body Barriers To Entrance Of Microorganismsmentioning
confidence: 99%
“…Também em culturas de leucócitos humanos, infectadas por diferentes vírus, tem sido possível evidenciar a produção de interferon 1,3,6,8,11,12,17,18,19,21,23,24,26 . O trabalho de Carver e Seto 5 mostra que culturas de fibroblastos humanos, depois de submetidas a estimulação com soros humanos contendo antígeno Austrália, tornam-se refretárias à multiplicação do vírus da doença de Newcastle.…”
Section: Unitermos: Antígeno Austrália (Hbs Agunclassified